The greater the investor attention, the better the post-IPO performance? A view of pre-IPO and post-IPO investor attention - Zhao, Yi; Wang, Nan; Zhang, Luyang; Sun, Baiqing; Yang, Yuchen (Research in international business and finance, 2022)
Post-IPO performance is a subject of concern in China’s registration system reform. IPOs in the registration system of the GEM and STAR Market between July 22, 2019, and October 31, 2020, are taken as samples to examine the impact of pre and post-IPO investor attention on post-IPO performance. The findings are as follows: (1) 60-day and 120-day BHARs are negative; (2) the longer investors purchase new shares and hold them, the greater their losses; (3) pre-IPO investor attention has a negative impact on short-term post-IPO performance; (4) post-IPO investor attention and negative posts have a negative impact on post-IPO daily returns; and (5) the impact is non-linear and it gradually increases with the increase in post-IPO investor attention. This study has implications for investors, regulators, and policymakers who can contribute to the healthy and stable development of China’s capital market and the smooth implementation of the registration system reform. [Display omitted] •Innovation has an impact on IPO short-term performance in the Chinese market.•The impact of investor attention on post-IPO daily returns is non-linear.•The negative impact of investor attention rises with increased investor attention.•The registration system reform can foster the development of the Chinese market.